(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a comparative analysis of the functioning of derivative vocabulary in Karakalpak and Russian proverbs and sayings. The structural and semantic features of derivational patterns in the two languages are examined, identifying common and nationally specific features. Particular attention is paid to the role of derivative words in shaping the imagery, evaluativeness, and cultural meanings of proverbs. The analysis revealed that despite typological differences (the inflectional nature of Russian and the agglutinative nature of Karakalpak), derivative vocabulary in both languages performs similar cognitive and axiological functions.